Surgery of the thyroid and parathyroid glands - Oertli, Daniel; Udelsman, Robert (Springer, 2012)
Now in a second updated edition, this unique in-depth reference covers all surgically relevant thyroid and parathyroid diseases and presents the latest on their management. International authorities discuss techniques and justify their favored approaches